Intralabyrinthine Schwannoma Mimicking Posterior Canalithiasis - Jonathan Olsgård Hansen; Niels Cramer West; Per Cayé-Thomasen (Journal of International Advanced Otology)
Intralabyrinthine schwannomas are a rare subgroup of vestibular schwannomas located within the membranous labyrinth of the inner ear and are known for their variable clinical presentations and symptoms. In the present study, we report on a patient with a persistent history of dizziness and positional vertigo, who was misdiagnosed with posterior canalithiasis. As hearing loss was not developed until late in the disease course, the patient was not properly diagnosed until magnetic resonance imaging revealed an intralabyrinthine schwannoma, which was not discovered on earlier imaging. In addition to the unusual clinical presentation, we describe the audio-vestibular profile of our patient. We suggest that a thorough vestibular evaluation, including caloric testing and a careful examination of the inner ear on imaging, is warranted in cases of treatment of refractory vertigo, even in patients where a diagnosis seems certain.